Proposed standard guideline for managing information systems (ISs) in libraries in Africa - Ocloo, P.E.D.; King, L. (Digital Library Perspectives, 2023)
Purpose – Libraries in Africa are adopting technology at a fast pace. However, literature has provided enough evidence of the many challenges libraries on the continent are facing in the use of the adopted information technology of which information systems (ISs) are major components. Literature also does not provide evidence of IS standard, policy or guideline at both national and international levels as a benchmark for the use of these systems. Therefore, this paper aims to propose an IS standard guideline as a guide for libraries in Africa to develop IS policies, standards or guidelines to help in effective use of IS in libraries. Design/methodology/approach – The researchers based their proposed standard guideline on the findings from their earlier research works and evidence from other existing literature as has been reviewed in this paper. Findings – Findings from the literature revealed that libraries in Africa face a number of challenges in the use of IS which can be categorised into four main areas, namely, financial challenges, technological and infrastructural challenges, human resource challenges and organizational challenges. Originality/value – This paper proposed an IS standard guideline to serve as a guide for libraries in Africa to develop IS policies, standards or guidelines to help in effective use of IS in libraries.
Research Article
Keywords: Libraries; Africa; Systems management; Information systems; Digital libraries; Library management